Design and Analysis of a 2-DOF Split-Stator Induction Motor - Si, Jikai; Feng, Haichao; Ai, Liwang; Hu, Yihua; Cao, Wenping (IEEE transactions on energy conversion, 2015)
A two degrees of freedom (2-DOF) actuator capable of producing linear translation, rotary motion, or helical motion would be a desirable asset to the fields of machine tools, robotics, and various apparatuses. In this paper, a novel 2-DOF split-stator induction motor was proposed and electromagnetic structure parameters of the motor were designed and optimized. The feature of the direct-drive 2-DOF induction motor lies in its solid mover arrangement. In order to study the complex distribution of the eddy current field on the ferromagnetic cylinder mover and the motor's operating characteristics, the mathematical model of the proposed motor was established, and characteristics of the motor were analyzed by adopting the permeation depth method (PDM) and finite element method (FEM). The analytical and numerical results from motor simulation clearly show a correlation between the PDM and FEM models. This may be considered as a fair justification for the proposed machine and design tools.